2016
DOI: 10.1039/c5ob02599k
|View full text |Cite
|
Sign up to set email alerts
|

Nitropyrrole natural products: isolation, biosynthesis and total synthesis

Abstract: Nitropyrrole-containing natural products are relatively rare in nature. Known examples are limited to the β-nitropyrrole-containing pyrrolomycins and α-nitropyrrole-containing nitropyrrolins and heronapyrroles. Their unique structures and interesting bioactivity are of ongoing interest to the chemistry community. This review describes the isolation, biological activity, biosynthesis and chemical synthesis of nitropyrrole-containing natural products reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This rare class of nitropyrroles has attracted some attention from synthetic chemists in recent years. Not least because of previous synthetic work and the promising effects against Gram-positive bacteria, nitropyrroles may represent interesting targets for further drug design [ 115 , 117 , 118 , 120 , 121 , 122 , 123 ].…”
Section: Non-halogenated Marine Pyrrole Alkaloidsmentioning
confidence: 99%
“…This rare class of nitropyrroles has attracted some attention from synthetic chemists in recent years. Not least because of previous synthetic work and the promising effects against Gram-positive bacteria, nitropyrroles may represent interesting targets for further drug design [ 115 , 117 , 118 , 120 , 121 , 122 , 123 ].…”
Section: Non-halogenated Marine Pyrrole Alkaloidsmentioning
confidence: 99%
“…Nitropyrrolins A ( 1 ), B ( 2 ), and D ( 4 ) exhibit cytotoxic activity toward the human colon carcinoma cell line HCT-116 ( 1 IC 50 31.1 μM, 2 IC 50 31.0 μM, and 4 IC 50 5.7 μM) . Inspired by the unique structures, promising biological activity and low abundance in nature, several groups have shown interest in the syntheses of these natural products . Stark et al , and our group have reported successful syntheses of heronapyrroles C and D in 2012 and 2014, respectively.…”
mentioning
confidence: 94%
“…The nitropyrrolins A–E 1 – 5 (Figure ) and heronapyrroles A–D 6 – 9 are structurally related pyrroloterpene natural products sharing an unusual 2-nitro-4-alkylpyrrole core . Nitropyrrolins A–E 1 – 5 were isolated from the culture broth of the MAR4 strain CNQ-509, obtained from a marine sediment sample collected off La Jolla, California by Fenical et al in 2010 .…”
Section: Introductionmentioning
confidence: 71%